The dialect of Gammalsvenskby: compiling a dictionary of an unexplored language (kimmar — kodest) - Mankov Alexander (Вестник Православного Свято-Тихоновского гуманитарного университета: Сериа III. Филология)
This paper presents new material for the dictionary of the present-day dialect of Staroshvedkoye (Gammalsvenskby), the only Scandinavian dialect on the territory of the former Soviet Union. The present-day state of this dialect has not been described in linguistic literature. The only source of data on Gammalsvenskby is fi eldwork with speakers of the dialect. The main objective of this work is to present material recorded in the interviews in the most complete way possible and to describe the state of the vocabulary and infl ection in the dialect. The entries include the following information: type of infl ection; translation; phrases, sentences and short texts illustrating the usage (with initials of the informants). In many cases full paradigms are given as well. They include all phonetic and morphological forms that have occurred in the interviews.